Restorative Justice and Social Reintegration of Juvenile Sexual Offenders: A Case Study of the Surakarta Juvenile Probation Office (BAPAS) (Legtimacy: Journal of Law and Islamic Law, 2025)
This study examines the legal and rehabilitative framework for juvenile sexual offenders in Surakarta, Indonesia, focusing on the role of the Balai Pemasyarakatan (BAPAS) under Law No. 11 of 2012 on the Juvenile Criminal Justice System. Despite intact family structures, many juveniles engage in rape due to inadequate parental supervision, restricted sexual education, and unmonitored exposure to digital pornography. The research objectives are to identify the underlying socio-psychological factors driving juvenile sexual offenses, evaluate current rehabilitation and restorative justice practices, and propose enhanced legal and social interventions to prevent recidivism. Employing a qualitative empirical approach, data were collected through in-depth interviews with community guidance officers at BAPAS Surakarta and supplemented by a comprehensive literature review of criminal and social control theories. Findings reveal that deficits in emotional regulation, impulse control, and moral comprehension exacerbated by early and unsupervised access to pornographic content constitute primary drivers of deviant sexual behavior among adolescents. Restorative justice measures, including diversion, community-based supervision, and trauma-informed counseling, demonstrate significant promise in reducing stigma and recidivism while fostering offender accountability and social reintegration. However, the effectiveness of these measures is often undermined by limited resources, insufficient coordination among stakeholders, and the absence of structured parental involvement programs. The study concludes by recommending the integration of mandatory healthy-sexuality curricula in schools, strengthened oversight protocols for digital media usage, and capacity building for BAPAS personnel to deliver holistic rehabilitation services. These reforms aim to align Indonesian juvenile justice practices with international child-rights standards and enhance long-term behavioral outcomes for young offenders.